Os sentidos do trabalho e carreira no setor público: um estudo sobre a trajetória profissional dos Assistentes em Administração de uma IES - GOMES , Raniele Cimara da Conceição (2023)
Work is an important element for building the personal and professional identity of the human being, it is through it that people attribute meanings and meanings to their occupations. Therefore, this project aims to analyze the meaning of work for administration assistants at the Federal University of Maranhão (UFMA) who built a career in an area different from their academic training. For this, the methodological path taken was qualitative, regarding the instruments, a sociodemographic questionnaire and a semi-structured interview script were applied. And to decode and analyze the interviewees' statements, Norman Fairclough's Social Theory of Discourse was used. As for the results and discussion, it was observed that among the reasons that influenced the choice for a career as an Assistant in Administration at UFMA, the desire for stability in the job market is presented in a punctual way, that is, in most cases the choice it did not happen by vocation but by financial necessity. With regard to the experiences of pleasure at work, the participants highlighted that the recognition and appreciation of the work they perform and the good relationship with the boss and other colleagues are pleasant factors. In the experiences of suffering, part of the assistants in administration, describe a feeling of fragmentation, regarding the adequacy of their own profile to the position held, they also punctuated the underused potential, as they carry out activities of a mid-level function and most of the workers have a higher position in different areas of their current professional activity, in addition, they also highlighted the excessive demands and the inappropriate physical structure. Regarding the adopted mediation strategies, the collective ones were not identified, the participants presented individual mobilization as a way of re-signifying and facing the suffering experienced in the work environment. Finally, this project sought to bring academic and social contributions, in order to promote reflections on the work of the Assistant in Administration, deconstructing prejudices and inspiring more research that investigates this category.